ANALISIS RASIO KEUANGAN DENGAN ROA SEBAGAI VARIABEL INTERVENING TERHADAP PERUBAHAN HARGA SAHAM PADA SEKTOR USAHA PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2018 – 2021 - Putri, Arinda Sinta; Karnadi, Karnadi; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2023)
Banking or financial institutions are establishments that amass funds from the public in banks and distribute these resources to the local community, contributing to the nation's developmental objectives. This research aims to assess and examine the impact of metrics such as CR, TATO, and DAR on stock price by means of analyzing ROA within the banking sector. The focus is on companies listed on the Indonesia Stock Exchange over the time span from 2018 to 2021. Using purposive sampling, a subset of 11 banking companies is selected for analysis. The research methodology encompasses the application of descriptive and inferential statistical techniques for data analysis and hypothesis testing. The outcomes of hypothesis testing conducted using the Smart PLS 3.0 application reveal that the influence of the CR on ROA is not statistically significant. Similarly, the TATO does not exert a significant impact on ROA, and the DAR also lacks a substantial influence on ROA. additionally, the CR does not demonstrate a noteworthy effect on stock price, while the TATO and DAR similarly do not yield a significant influence on stock price. The findings from the hypothesis testing related to indirect effects indicate that the CR does not significantly affect stock price through its impact on ROA, similarly, the TATO effect on stock price through ROA is not statistically significant, and the DAR influence on stock price through ROA is also not statistically significant.